Effectiveness of online advertisement on the behavior of stripling in purchasing the lifestyle products: A comparative study of urban and rural college students - Gowda Madahalli Krishnegowda, Venugopal; Ngawang Tsepak (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2023)
The 21st century has shown remarkable changes in the Indian marketing landscape due to internet adoption and technological advancements. The young generation's embrace of online activities has transformed the consumer behavior. With 840 million internet users, including 448 million active users on social media, online advertising has become a powerful tool to attract attention and drive product purchases. Simultaneously, E-commerce platforms have revolutionized access to goods and services. In this view, this study focuses on understanding the impacts of online advertisements on the purchasing behavior of the young generation, specifically in terms of lifestyle products. Researchers explored how online advertisement has influenced decision-making processes and uncovered the motives driving internet usage among young adults. Additionally, the study assessed the perceptions of trustworthiness between online and offline products. 200 respondents from rural and urban colleges were analyzed to identify the key factors determining the purchasing decisions among young adults. Price, discounts, perceived needs, and timeliness are some of the factors explored. The findings revealed the impacts of online advertisements on product purchases among college students in both rural and urban settings. Insights into young adults' motivations and preferences are invaluable for businesses to effectively engage with this dynamic consumer base. Armed with these findings, businesses can develop targeted marketing strategies that resonate with the evolving digital landscape, ensuring success in India's digitally-driven market.